Determinan Balita Stunting di Jawa Timur: Analisis Data Pemantauan Status Gizi 2017 - Agung Dwi Laksono; Hario Megatsari (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Stunting in early life will have adverse functional consequences, including poor cognition and low levels of education. The study aimed to determine the determinants of stunting toddlers in East Java.Methods: The study uses secondary data from the 2017 PSG. Using the multi-stage cluster random sampling method, a sample of 10,814 toddlers aged 0-59 months was taken. The analyzed variables consisted of the dependent variable nutritional status of toddlers, 7 independent variables: residence, toddler age, mother's age, marital status of mothers, mother's education level, and working status of mothers. Determination of determinants using the Binary Logistic Regression test.Results: Toddlers living in urban areas were 0.855 times more at risk of stunting compared to toddlers living in rural areas (OR 0.885; 95% CI 0.798-0.980). Toddlers who have mothers with elementary education and below 2.206 times have more risk of stunting compared to toddlers who have mothers with college education (OR 2.206; 95% CI 1,835-12,651). Toddlers who have mothers with junior high school education were 1,676 times more likely to have stunting risk compared to toddlers who have mothers with tertiary education (OR 1.676; 95% CI 1.395-2.015). toddlers who have mothers with high school education are 1,266 times more likely to have stunting risk compared to toddlers who have mothers with tertiary education (OR 1,266; 95% CI 1,058-1,514).Conclusion: There were 4 variables that have proven to be significant as determinants of stunting in East Java Province, namely residence, age of toddler, age of toddler mother, and mother's level of educationABSTRAK Latar Belakang: Stunting dalam kehidupan awal akan mempunyai konsekuensi fungsional yang merugikan, termasuk kognisi yang buruk dan tingkat pendidikan yang rendah. Variabel ini perlu diperhatikan karena menurut Unicef, ada faktor sosial budaya yang berperan dalam terjadinya permasalahan stunting. Penelitian ditujukan untuk menentukan determinan balita stunting di Jawa Timur.Metode: Penelitian menggunakan data sekunder survei Pemantauan Status Gizi tahun 2017 (PSG 2017). Dengan metode multi-stage cluster random sampling, diambil sampel 10.814 balita berusia 0-59 bulan. Varibel yang dianalisis terdiri dari variabel dependen status gizi balita, 7 variabel independen: tempat tinggal, umur balita, umur ibu balita, status perkawinan ibu balita, tingkat pendidikan ibu balita, dan status bekerja ibu balita. Penentuan determinan dengan menggunakan uji Regresi Logistik Biner.Hasil: Balita yang tinggal di daerah perkotaan 0,855 kali lebih memiliki risiko stunting dibandingkan dengan balita yang tinggal di daerah pedesaan (OR 0,885; 95% CI 0,798-0,980). Balita yang memiliki ibu dengan pendidikan SD ke bawah 2,206 kali lebih memiliki risiko stunting dibandingkan dengan balita yang memiliki ibu dengan pendidikan perguruan tinggi (OR 2,206; 95% CI 1,835-12,651). Balita yang memiliki ibu dengan pendidikan SLTP 1,676 kali lebih memiliki risiko stunting dibandingkan dengan balita yang memiliki ibu dengan pendidikan perguruan tinggi (OR 1,676; 95% CI 1,395-2,015). balita yang memiliki ibu dengan pendidikan SLTA 1,266 kali lebih memiliki risiko stunting dibandingkan dengan balita yang memiliki ibu dengan pendidikan perguruan tinggi (OR 1,266; 95% CI 1,058-1,514).Kesimpulan: Ada 4 variabel yang terbukti signifikan sebagai determinan kejadian stunting di Provinsi Jawa Timur, yaitu tempat tinggal, umur balita, umur ibu balita, dan tingkat pendidikan ibu balita.